1995
DOI: 10.1113/expphysiol.1995.sp003869
|View full text |Cite
|
Sign up to set email alerts
|

The secretion of parathyroid hormone‐related protein in the saliva of sheep and its effects on the salivary clearance of phosphate, calcium, magnesium, potassium and sodium ions

Abstract: SUMMARYParathyroid hormone-related protein (PTHrP(1-34)) was infused into five sheep, each fitted with a large rumen cannula. After infusion, significant increases were observed in the total and ionized calcium concentrations in plasma but not in saliva. In contrast, significant decreases in the plasma concentrations of phosphate and potassium and corresponding increases in their salivary concentrations and clearance rates were observed. The salivary concentration of endogenous PTHrP(1-34) was significantly gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…This has been confirmed by the findings reported by Dua et al [33] on the sheep salivary gland. These authors [33] observed after PTHrP infusion (1-34) a significant increase in the total and ionized calcium concentration in plasma but not in saliva.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This has been confirmed by the findings reported by Dua et al [33] on the sheep salivary gland. These authors [33] observed after PTHrP infusion (1-34) a significant increase in the total and ionized calcium concentration in plasma but not in saliva.…”
Section: Discussionsupporting
confidence: 89%
“…This has been confirmed by the findings reported by Dua et al [33] on the sheep salivary gland. These authors [33] observed after PTHrP infusion (1-34) a significant increase in the total and ionized calcium concentration in plasma but not in saliva. In contrast, they noted a significant decrease in the plasma concentration of phosphate and potassium, and a corresponding increase in their salivary concentrations and clearance rates.…”
Section: Discussionsupporting
confidence: 89%
“…This effect may partly be a consequence of the infusion because a 0.9 % sodium chloride or a 5 % dextrose control solution alone induced hypophosphatemia (F enwick and D aniel 1992b, c). However, the increase of serum PTH concentration in response to the decrease of serum Ca (P otts et al 1968) may also be involved because PTH stimulates P i secretion in the saliva of sheep (C lark et al 1975; W right et al 1984; D ua et al 1995) and urine of sheep (B arlet and C are 1972) and cows (M ayer et al 1966, 1968). It is well established that the salivary route is the most important P i secretory pathway in ruminants (B reves and S chröder , 1991; C are 1994; B arlet et al 1995) whereby 1,25‐dihydroxyvitamin D (1,25‐(OH) 2 D) modulates this process in decreasing salivary P i (M anas ‐A lmendros et al 1982, R iad et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…P1NP and TRAcP 5b [38] show high individuality (individuality index (II) < 0.6) equal to 0.12 and 0.56 respectively; the variation of values for each individual assessed occupies only a small part of the distribution of values for the whole group. In these cases, there is the risk of considering the value of an analyte in an individual to be improperly physiological and significantly far from its homeostatic set point but still included within the range of values obtained.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has inspired various studies that have focused on the role of PTHrP in mediating osteoclastogenesis [37]. In subjects in the development age, the values on the biological variability of PTHrP in saliva, the low individuality, the higher critical difference with respect to the other evaluated biomarkers and the concentrations with secretion dynamics similar to those of the serum could be explained according to the constant local paracrine production related to the need for a regulatory mechanism on bone formation and tooth growth [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%